Crystallisation of Calcium Oxalate Solids in the Presence of Tetrazoles - McMulkin, Calum (Curtin University, 2017)
A series of tetrazoles-containing molecules were investigated for their impact on calcium oxalate monohydrate (COM) crystallisation for the first time. COM is the main constituent of kidney stones, a common pathological mineral in humans. The tetrazole series was found to inhibit the morphology, crystal growth and nucleation of COM directly through selective adsorption or by a complexation mechanism, to varying degrees. Structural trends and which of the tetrazole molecules as crystal growth modifiers were confirmed.